Metal Anodes: Pristine or Highly Defective? Understanding the Role of Graphene Structure for Stable Lithium Metal Plating (Adv. Energy Mater. 3/2019). Issue 3 (17th January 2019) - Liu, Wei; Xia, Yuting; Wang, Wenwu; Wang, Yizhe; Jin, Jialun; Chen, Yungui; Paek, Eunsu; Mitlin, David
Abstract : In article number1802918, Wei Liu, Yungui Chen, David Mitlin and co‐workers examine the role of graphene structure and chemistry in stabilizing Li metal plating, showing that defects are bad. An ideal graphene membrane will allow for dense nucleation of Li while shielding it from reactions with the electrolyte. Importantly, graphene itself should be non‐catalytic towards solid electrolyte interphase (SEI) formation, since pre‐existing SEI promotes dendrites.